PENGARUH PROFITABILITAS, STRUKTUR KEPEMILIKAN DAN REPUTASI KAP TERHADAP NILAI PERUSAHAAN (Studi Kasus Perusahaan Kimia di Bursa Efek Indonesia Tahun 2013 – 2017) - Akhmad Zaini; Yuli Chomsatu; Suhendro Suhendro (Universitas Slamet Riyadi, 2020)
This study aims to analyze the effect of profitability on firm value, analyze the influence of inside ownership on firm value, analyze the influence of institutional holdings on firm value, and analyze the influence of KAP reputation on firm value in chemical companies listed on the Indonesia Stock Exchange in 2013-2017. This research is quantitative research. Where the data obtained is in the form of numbers which are then processed and analyzed to get an overview and relationship between the variables used. Data analysis used in this study is multiple linear regression analysis using SPSS as a tool. The results of this study indicate that there is a positive and significant effect on profitability on firm value, there is a positive and significant influence on the ownership of firm value, there is a positive and significant influence of institutional holdings on firm value, and there is a positive and significant influence on the firm's KAP reputation.